2015
DOI: 10.3813/aaa.918824
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro and Numerical Investigations of the Influence of a Vocal-Tract Resonance on Lip Auto-Oscillations in Trombone Performance

Abstract: Controlling the acoustic impedance of the upstream airways in brass instrument performance may be an important factor influencing the efficiency of the sound production process. Because of the complex characteristics of the lip-valve oscillator, the conditions under which a vocal-tract resonance may be favorable to the sustain of lip auto-oscillations are not easy to determine. In order to investigate this aspect of brass performance, an experimental method based on an active control approach is applied to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In brass instruments, the lip excitation mechanism is commonly modeled by a simple one-degree-of-freedom mechanical oscillator, non-linearly coupled to the air-column of the instrument by a flow model [4][5][6]. More advanced representations of this model have been considered by concentrating on the fluidstructure interaction between the air-jet and the lips [7], the number of degrees of freedom for the lips [8,9], the acoustical interaction with the upstream airways [10,11], or the nonlinear propagation inside the bore of the instrument [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In brass instruments, the lip excitation mechanism is commonly modeled by a simple one-degree-of-freedom mechanical oscillator, non-linearly coupled to the air-column of the instrument by a flow model [4][5][6]. More advanced representations of this model have been considered by concentrating on the fluidstructure interaction between the air-jet and the lips [7], the number of degrees of freedom for the lips [8,9], the acoustical interaction with the upstream airways [10,11], or the nonlinear propagation inside the bore of the instrument [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The vocal tract modelling is also critical, and there are contributions in this aspect based on tube models [18,19]. These models are commonly used for modelling musical instruments, and the influence of the vocal tract on trombone performance can be visited in [20]. Freour et al [20] investigated the effect of vibroacoustic interaction in the trombone and found that there is no clear difference in perception between instruments fabricated with different materials, and that the selection of material is more related to aesthetic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…These models are commonly used for modelling musical instruments, and the influence of the vocal tract on trombone performance can be visited in [20]. Freour et al [20] investigated the effect of vibroacoustic interaction in the trombone and found that there is no clear difference in perception between instruments fabricated with different materials, and that the selection of material is more related to aesthetic aspects. However, Kausel et al [21] claimed that even though the material does not change the timbre of the sound, it does emphasize high frequencies in some way.…”
Section: Introductionmentioning
confidence: 99%
“…Physical modeling is a valuable strategy in order to study numerically the response of a musical instruments [1]. In the case of brass instruments, various studies have focused on the modeling and simulation of the brass player and his/her instrument [2][3][4][5][6][7][8][9][10]. Some techniques such as numerical continuation are particularly relevant in order to compute periodic solution branches of wind instrument models [11].…”
Section: Introductionmentioning
confidence: 99%